Effectiveness Discovery Learning and Learning Cycle 5E Integrated Virtual Lab on Learning Outcomes in Acid-Base - Elisabeth Siallagan; Erna Sari Dewi Sianturi; Jelita Harahap; Nora Susanti (Universitas Negeri Medan, 2024)
This study was conducted to determine the effectiveness of the Discovery learning and Learning Cycle 5E learning models and to see the differences in academic performance from the two models. The method used is experimental. The population in this study were students of class XI Science at SMAN 17 Medan and the samples were class XI Science 4 as experimental class 1 and XI Science 3 as experimental class 2. The research results show that the Discovery Learning model is effective in improving academic performance as evidenced by the average N-gain value of 0.759 in the high category, the Learning Cycle 5E model is effective in academic performance as evidenced by the average N-gain value of 0.751 with high category and there is a significant difference in the academic performance of students who are taught using the Discovery Learning and Learning Cycle 5E models integrated with virtual labs on acid-base material as proven by carrying out by Independent Sample T-test so the output can obtained value of sig is 0.011<0.05.